Proposing Three Potential-Interest Development Paradigm as the Local People Involvement Strategy for Tourism Destination Sustainability in Indonesia - GIYOTO, Giyoto; INDERASARI, Elen; LESTARI, Sri; NURJANAH, Hidayatul; PRAYITNO, Harun Joko; SALAM, Amri Adi Nur (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).10, 2022)
This paper proposing the destination development paradigm based on the blend among the different potential interests of nature, physical cultural products, and local beliefs in a single destination. This blend governs the way how the management, visitors, local people should do in order to keep the sustainability and local people empowering. This paradigm was proved in Lombok and Java Indonesia which have engaged double different potential interests in a single destination along hundreds years. The research was done qualitatively, by interviewing the purposive respondents to confirm the open questionnaires relating the participations and responses of the local people or communities. The 137 purposive samples are based on their engagements in the tourism. The results show that: 1) the most sustaining interests are the blend of interests among the local beliefs, the nature, and physical cultural products; 2) the development paradigm of Sunan Kudus in Java is Bipots, while Sembalun, Bayan in Lombok and Muria in Java has Tripots development paradigm; 3) The management are involving local people daily activities, local communities and agents, as well as visitors in developing the destination; 4) The high positive responses of the local people, through which the interests are their daily concerns, support in sustaining the destinations, which are intersecting the three different potential interests; proposed as Tripots Paradigm.